2015
DOI: 10.1159/000439056
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Role of Dynamic Hyperinflation in Patients with Severe Chronic Obstructive Pulmonary Disease

Abstract: Background: Dynamic hyperinflation due to increased respiratory frequency during exercise is associated with limitations in exercise capacity in patients with moderately severe chronic obstructive pulmonary disease (COPD). Objectives: The present study assessed whether the manually paced tachypnea (MPT) test, sitting at rest, induces dynamic hyperinflation correlating with exercise capacity in patients with very severe COPD. Methods: Dynamic hyperinflation was induced by the MPT test, using a breathing frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…Petrovic et al evaluated effects of IMT on inspiratory capacity (IC) and inspiratory fraction (IC/TLC) which are two clinical parameters reflecting hyperinflation. They demonstrated that in comparison with usual care, IMT improved more hyperinflation which is an important mechanism explaining dyspnea in COPD . It provides a novel and interesting hypothesis about the mechanisms explaining efficacy of IMT on dyspnea.…”
Section: Discussionmentioning
confidence: 93%
“…Petrovic et al evaluated effects of IMT on inspiratory capacity (IC) and inspiratory fraction (IC/TLC) which are two clinical parameters reflecting hyperinflation. They demonstrated that in comparison with usual care, IMT improved more hyperinflation which is an important mechanism explaining dyspnea in COPD . It provides a novel and interesting hypothesis about the mechanisms explaining efficacy of IMT on dyspnea.…”
Section: Discussionmentioning
confidence: 93%
“…The MPT test was first used by Gelb et al [1], in 16 chronic obstructive pulmonary disease (COPD) patients. Gelb et al [1] showed that DH with MPT was similar to DH with a CPET, if a subject breathed at twice the resting respiratory rate for 20 s. Since, the MPT test has been used in multiple studies to investigate the response to various bronchodilators [1-4], the development of DH during exacerbations [5], the role of DH in COPD [6], and the development of DH over the course of years [7]. Despite its increasing use as a valid measurement tool, only little is known about the accuracy of the MPT.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, one could discuss whether the test used in the current trial is the optimal standard to detect dynamic hyperinflation. 13 , 31 Based upon ethical arguments, the study team chose not to perform the more commonly used and better validated exercise test during the acute distress of severe exacerbation requiring admission.…”
Section: Discussionmentioning
confidence: 99%